Polyassociative thermodynamic model of A²B⁶ semiconductor meltand phase equilibria in Cd-Hg-Te system. 4. p-T-x diagram of Cd-Hg-Te system - Moskvin, P.P.; Khodakovsky, V.V.; Rashkovets’kyi, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
p −T− x diagram of Cd-Hg-Te system is analyzed in the framework of the polyassociative solution model. The temperature dependence of the dissociation constant for ternary complexes, which describes the mixing effects, was determined using the low temperature data on phase equilibrium in the system. A satisfactory agreement between calculated and experimental data of various works about phase equilibrium was attained.